Issues and challenges in the development of deca-dodecasil 3 rhombohedral membrane in CO2 capture from natural gas - Muhammad, M. (Bellwether Publishing, Ltd., 2015)
Removal of CO2 from natural gas using a membrane-based process has been adopted on an industrial scale, and about 200 membrane separation plants have been installed all over the world. In industry, inorganic membranes are preferred over the polymeric and mixed matrix membranes in CO2 separation from natural gas because of their good chemical stability and high separation performance. Among all inorganic membranes, deca-dodecasil 3 rhombohedral zeolite (DDR) membrane exhibits the highest selectivity in CO2 separation from natural gas. However, synthesis of DDR membranes requires a long duration, with a minimum of 25 days. Therefore, reduction of duration in the synthesis of the DDR membrane remains a challenging issue. In this review, separation performance of polymeric, mixed matrix and inorganic membranes are compared. Synthesis methods of DDR membranes and their performance in CO2separation reported by various researchers are discussed. The challenges and issues related to the formation of DDR membranes are also included. In conclusion, the future direction and perspective on the development of DDR membranes for CO2 separation are summarized. Copyright Â© Taylor & Francis Group, LLC.